Modeling collective cell migration in geometric confinement - Tarle, Victoria; Gauquelin, Estelle; Vedula, S. R.K.; D'Alessandro, Joseph; Lim, C. T.; Ladoux, Benoit; Gov, Nir S. (Physical Biology, 2017)
Monolayer expansion has generated great interest as a model system to study collective cell migration. During such an expansion the culture front often develops 'fingers', which we have recently modeled using a proposed feedback between the curvature of the monolayer's leading edge and the outward motility of the edge cells. We show that this model is able to explain the puzzling observed increase of collective cellular migration speed of a monolayer expanding into thin stripes, as well as describe the behavior within different confining geometries that were recently observed in experiments. These comparisons give support to the model and emphasize the role played by the edge cells and the edge shape during collective cell motion.
CRIS-Team Scopus Importer:2024-02-19
Keywords: collective cell migration; curvature-force feedback; leader cells